ESTIMATION OF POLLUTANT CONCENTRATIONS AT ROAD INTERSECTION IN SERI ISKANDAR - MOHD MUKHTAR, MUHAMMAD ZAID (IRC, 2016)
Air pollution is one of the major environmental problem, which becomes a concern to public health. The origin of the air pollution is mostly from combustion engines regardless of type and size of the engines. The main pollutant gases produce by the combustion engine are carbon monoxide (CO), carbon dioxide (CO2), unburned hydrocarbon (HC) and nitrogen oxides (NOx). There is few research conducted to investigate emitted pollutant at a road intersection. At the road intersection, a vehicle normally will experience deceleration, idling and acceleration, which would contribute to air quality problem. Pollutant from idling vehicle at the road intersection are likely will give significant impact to the quality of air. Hence, it is important to identify the most polluted emission and the concentration level of harmful pollutant whether it gives significant impact on safety and health for people at the road intersection perimeter. The aim of this study determine the concentration level of carbon monoxide (CO) and carbon dioxide (CO2) at signalized intersection of the study area